2016
DOI: 10.1016/j.jadohealth.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Families Matter: Social Support and Mental Health Trajectories Among Lesbian, Gay, Bisexual, and Transgender Youth

Abstract: Purpose Lesbian, gay, bisexual, and transgender (LGBT) adolescents are at greater risk for mental health problems than their heterosexual peers, in part due to victimization. Social support, particularly from families, has been identified as an important promotive factor. However, little is known about how LGBT youth experience multiple forms of support or how early support predicts mental health across adolescence and into young adulthood. Methods In an analytic sample of 232 LGBT youth aged 16–20 years at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(186 citation statements)
references
References 35 publications
9
164
1
12
Order By: Relevance
“…However, it showed a trend towards a negative association with distress ( p = .10) and was significant in correlational analyses. Given that social support has been found to be especially important early in adolescence (McConnell et al, 2016) and victimization is a stronger predictor of distress over time (Birkett, Newcomb, & Mustanski, 2015), the older age of our sample may account for this nonsignificant fining.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, it showed a trend towards a negative association with distress ( p = .10) and was significant in correlational analyses. Given that social support has been found to be especially important early in adolescence (McConnell et al, 2016) and victimization is a stronger predictor of distress over time (Birkett, Newcomb, & Mustanski, 2015), the older age of our sample may account for this nonsignificant fining.…”
Section: Discussionmentioning
confidence: 89%
“…Data collection was conducted in 2013 and 2014. Further description is reported elsewhere (Birkett, Newcomb, & Mustanski, 2015; McConnell, Birkett, & Mustanski, 2016; McConnell, Birkett, & Shattell, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Recently, research on transgender youth has expanded to the family, particularly focusing on parents and caregivers (Dierckx, Motmans, Mortelmans, & T’sjoen, 2016; Rahilly, 2015; Sansfacon, Robichaud, & Dumais-Michaud, 2015). As for all youth, caregivers are understood to significantly impact the well-being of transgender youth (McConnell, Birkett, & Mustanski, 2016; Ryan, Russell, Hhuebner, Diaz, & Sanchez, 2010). A qualitative study of resiliency among transgender youth found that participants described their families as a primary source of resilience (Singh, Meng, & Hansen, 2014).…”
Section: Family Perspectivementioning
confidence: 99%
“…Research has suggested that family factors play a significant role in health disparities among sexual minority youth and young adults (Bouris et al., ; McConnell, Birkett, & Mustanski, ; Needham & Austin, ; Padilla, Crisp, & Rew, ; Rosario, Schrimshaw, & Hunter, ; Ryan, Huebner, Diaz, & Sanchez, ; Ryan, Russell, Huebner, Diaz, & Sanchez, ; Willoughby, Doty, & Malik, ). Rosario, Hunter, Maguen, Gwadz, and Smith () suggests that the sexual identity development and integration, or coming out , process influences many adaptation and health related behaviors of youth, such as self‐esteem, psychological functioning, and sexual health and is, in turn, affected by the stressors and strengths of the youth, their family, and their community (Rosario et al., ).…”
Section: Background and Significancementioning
confidence: 99%
“…McConnell et al. () found that youth from families who experience low levels of social support reported more psychological distress over time, even when controlling for experiences of victimization.…”
Section: Background and Significancementioning
confidence: 99%